A Power Spectral Study of PHANGS Galaxies with JWST MIRI: On the Spatial Scales of Dust and Polycyclic Aromatic Hydrocarbons - Charlie Lind-Thomsen; Albert Sneppen; Charles L. Steinhardt (The Astrophysical Journal)
The interstellar medium (ISM) consists of a diversity of structures across a range of spatial scales, intimately tied to galactic evolution. In this work, Fourier analysis is used to characterize the spatial structures of dust and polycyclic aromatic hydrocarbons (PAHs) in the ISM of Physics at High Angular Resolution in Nearby GalaxieS (PHANGS) James Webb Space Telescope (JWST) galaxies, observed in the four photometric mid-infrared filters from F770W to F2100W (i.e., 7.7–21 μ m). We quantify the abundance of structure on different spatial scales using the power-law slope, α , of the spatial power spectra. The distribution of α across all length scales differs significantly between filters, with steeper slopes for PAH-dominated filters ( ${α }_{{\rm{F}}770{\rm{W}}}=2.1{9}_{-0.15}^{+0.16}$ , ${α }_{{\rm{F}}1130{\rm{W}}}=1.8{8}_{-0.37}^{+0.25}$ ) and shallower for the dust continuum ( ${α }_{{\rm{F}}1000{\rm{W}}}=1.4{8}_{-0.47}^{+0.33}$ , ${α }_{{\rm{F}}2100{\rm{W}}}=0.9{4}_{-0.28}^{+0.23}$ ). The distribution of α across galaxies is narrower for PAH-dominated than for thermal dust-dominated bands, highlighting that PAHs trace photodissociation regions dominated by similar physical processes, whereas dust structures are an integrated property over the diverse evolutionary histories of their host galaxies. Unlike dust structures, PAH-sensitive bands display a break in the power spectrum: below a characteristic scale, ${\ell }_{0}=160\,{pc}_{-50\,pc}^{+110\,pc}$ , PAH structures are suppressed.